Micro-service solution of operator’s business platform - Liyun YAN; Xinzhang YANG; Zhenwei HE; Ling ZHANG; Shaoxin HOU (Dianxin kexue)
The high concurrency and uninterrupted nature of internet applications requires high performance and scalability.Micro-service have become the preferred architecture for internet applications.Under the background of business-driven and “internet +” transformation,it is imperative for operators to implement micro-service transformation of traditional business platforms.The status and requirements of the operator's business platform were analyzed.The micro-service design scheme of the business platform was explained from several dimensions of micro-service splitting,micro-service architecture,interface design and DevOps,combining the key technologies of micro-service and benchmarks multiple technologies.